How to assess the volume of a DIEP flap using a free online calculator: The DIEP V (volume) method. Issue 10 (October 2018) - Razzano, Sergio; Taylor, Ryan; Schonauer, Fabrizio; Figus, Andrea
Summary: Introduction: Among the few methods available, none is able to determine accurately the volume of a DIEP flap. Specimen weight is commonly used to assess the amount of flap needed to reconstruct a breast, but the density of breast is different from that of abdominal tissues; therefore, the volume should be used as a unique unit of measure. The purpose of this study was to provide a simple method to calculate the predicted volume of a DIEP flap in order to match the volume of the breast being reconstructed. Material and Method: We hypothesised that the shape best resembling a DIEP flap was a truncated pyramid. Based on this shape, we tailored 30 DIEP flap models using the discarded tissue after unilateral DIEP flap breast reconstructions. The awaited volume (AV) of the models was calculated with a free online calculator measuring the length and height with a ruler, and width (fat thickness) with Ultrasound (US). The real volume (RV) of the models was calculated using water displacement method. AV and RV were compared and statistical analysis was performed. Results: The mean difference between the AV and the RV was not statistically significant with a mean estimation error of 6.75%. When the AVs were plotted against the RVs, the two data sets were highly statistically correlated (correlation coefficient ( r = 0.997). Conclusions: The proposed tool can be a useful, precise, easy and accessible tool to improve the current DIEP flap size assessment improving outcomes for both surgeons and patients.